A rapid-cycle assessment strategy for understanding the opioid overdose epidemic in local communities. Issue 4 (2nd October 2021) - Taubenberger, Simone; Spencer, Noelle; Chang, Judy C.; Paul, Nicole; Fabre, Shelcie; Jagessar, Bhavita; Trimble, Daly; Roberto, Raisa; Gill, Puneet; Hulsey, Eric; Arnold, Aaron; Hacker, Karen
Abstract: Background: Certain communities in the United States experience greater opioid-involved overdose mortality than others. Interventions to stem overdose benefit from contextual understandings of communities' needs and strengths in addressing the opioid crisis. This project aims to understand multiple stakeholder perspectives on the opioid epidemic in communities disproportionately affected by opioid-involved overdose mortality. Methods: We performed a rapid-cycle qualitative assessment study utilizing in-depth interviews with community stakeholders and observations of community meetings in eight communities in Allegheny County, Pennsylvania, USA, disproportionately impacted by opioid-involved overdose mortality. Stakeholder categories included: current and past illicit users of opioids; medical and social service providers; emergency medical services; law enforcement; spouse or other family members of illicit users/former users of opioids; government officials; school officials; community members. Content analysis was utilized to identify themes and answer study questions. Regular feedback to stakeholders was provided to support targeted interventions. Results: We performed semi-structured, in-depth interviews with 130 community stakeholders and 29 community meeting observations in 2018–2019. Participants perceived similar economic and social determinants as origins of the opioid overdose epidemic including lack of economic resources, loss of jobs, transient populations and dilapidated housing. However, they differed in their awareness of and attention to the epidemic. Awareness was dependent on the visibility of opioid use (presence of paraphernalia litter, location of drug users, media coverage, and relationship to users). Overall, there was good knowledge of naloxone for opioid overdose reversal but less knowledge about local syringe services programs. Perceptions of harm reduction efforts were ambivalent. Conclusions: Members of communities impacted by the opioid epidemic perceived that economic downturn was a major factor in the opioid overdose epidemic. However, the varied beliefs within and between communities suggest that interventions need to be tailored according to the cultural norms of place.